The role of social media influencers and eWOM in driving purchase intention: insights from SMEs in the gamarra cluster - Medina, Franco (2025)
This study examines the influence of social media influencers (SMI) and electronic word-of-mouth (eWOM) on purchase intention (PI) within small and medium-sized enterprises (SMEs) agglomerated in the Gamarra textile cluster in Lima, Peru. Grounded in cluster theory and source credibility theory, the research aims to understand how these digital marketing strategies shape cluster-level brand trust (BT) and consumer brand engagement (CBE), ultimately influencing customer purchase decisions in one of the clustered SEMs. Data were collected via an online survey of 395 followers who engage with influencers frequently posting content related to the cluster. Using partial least squares structural equation modelling (PLS-SEM), the study confirms that both SMI and eWOM positively affect BT and CBE, although SMI has a stronger impact on CBE than eWOM. Additionally, CBE was found to be a more significant driver of PI than BT, reinforcing its role as a key construct in digital marketing effectiveness. The findings contribute theoretically by extending the application of source credibility and cluster theories to the context of agglomerated SMEs using shared branding. Practically, the study suggests that cluster managers should prioritise influencer-based strategies to build engagement and trust, especially when marketing budgets are limited. These insights offer actionable guidance for SMEs seeking to compete more effectively through clustering digital branding initiatives.